Executive Committee Minutes 2008-01-31 - Academic Senate:::::::::
Planning for Focus the Nation, Alumni on Senate-Talk, Faculty Eligible for Emeritus Status, Excellence in Teaching Award Committee, Course Outline Policy revision, RTP policy revision